Monitoring of fatigue damage using ultrasonics and finite element analysis - Hrairi, Meftah; Mohammad, Masturah; Ismail, Siti Maisara (Trans Tech Publications, Switzerland, 2012)
This study investigated the initiation and propagation of cracks until fracture of aluminum alloy 7075 under cyclic loadings. Tests were conducted to generate fatigue failures from 1×103 to 4×104 cycles at 10 Hz. Nondestructive ultrasound technique was used to detect the presence of any crack as well as its growth. Finite element analysis was conducted in order to assess the ability to predict fatigue crack initiation behavior. The results obtained from the fatigue test were compared to those obtained using ANSYS and a good agreement between the two was observed.